2021
DOI: 10.1111/tbed.14370
|View full text |Cite
|
Sign up to set email alerts
|

A new canine distemper virus lineage identified from red pandas in China

Abstract: Canine distemper virus (CDV) is a highly contagious virus that causes multi-systemic, sub-clinical to fatal diseases in a wide range of carnivore species. Based on the sequences of the haemagglutinin (H) gene, CDV strains have been classified into 18 major genetic lineages. In this study, we characterized the genomes of CDV isolated from the lungs of two dead red pandas in China. Histopathological and immunohistochemical analyses revealed damage due to viral infection in these lungs. The two strains showed a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 70 publications
2
19
0
Order By: Relevance
“…Intracytoplasmic and intranuclear inclusions were detected in bronchial epithelial cells and syncytial cells. These ndings in the lungs are consistent with previous studies in different animal species, including dogs, where the presence of CDV is observed (Pratakpiriya 2017;Michelazzo et al 2021;Wang et al, 2021b).…”
Section: De Nitive Diagnosis Of CDV Is Made By Histopathological Ndin...supporting
confidence: 92%
“…Intracytoplasmic and intranuclear inclusions were detected in bronchial epithelial cells and syncytial cells. These ndings in the lungs are consistent with previous studies in different animal species, including dogs, where the presence of CDV is observed (Pratakpiriya 2017;Michelazzo et al 2021;Wang et al, 2021b).…”
Section: De Nitive Diagnosis Of CDV Is Made By Histopathological Ndin...supporting
confidence: 92%
“…CDV is estimated to be present in most countries, and primarily infects Canid species. The virus also infects other animal species belonging to the order Carnivora (including Felidae, Mustelidae, Procyonidae, Ursidae, Phocidae, Viverridae, Hyaenidae, Ailuridae, Mephitidae, and Otariidae) and other orders (Artiodactyla, Primates, Rodentia, and Pilosa) 42–48 . However, studies on CDV infection in wild animals living in endemic areas have shown differences in mortality rates and possession of anti‐CDV antibodies among closely related species 49,50 .…”
Section: Epidemiology Of Current Morbillivirus Speciesmentioning
confidence: 99%
“…The strains of CDV are classified by different regions, and each lineage is subdivided into numbers. Currently, America‐1 to 5, Arctic‐like, Asia‐1 to 4, India‐1/Asia‐5, Asia‐6, Africa‐1 and ‐2, Caspian, European Wildlife, Europe/South America‐1, South America‐2 and ‐3, and Rockborn‐like have been reported 47,54–58 . Each CDV strain has its own characteristic amino acid substitutions 59 .…”
Section: Epidemiology Of Current Morbillivirus Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…CDV is an enveloped virus and contains a non-segmented, single-stranded negative-sense RNA genome, which encodes for six proteins: nucleocapsid (N), phospho- (P), matrix (M), fusion (F), hemagglutinin (H) and polymerase (L) proteins. Thus far, at least 20 genotypes of CDV have been identified, including the recently discovered Caspian and Asia 4–6 genotypes 4 8 .…”
Section: Introductionmentioning
confidence: 99%